2019
DOI: 10.1289/ehp4583
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nanomolar Deltamethrin on the Hallmarks of Primary Cultured Cortical Neuronal Network and the Role of Ryanodine Receptors

Abstract: Background:The pyrethroid deltamethrin (DM) is broadly used for insect control. Although DM hyperexcites neuronal networks by delaying inactivation of axonal voltage-dependent Na+ channels, this mechanism is unlikely to mediate neurotoxicity at lower exposure levels during critical perinatal periods in mammals.Objectives:We aimed to identify mechanisms by which acute and subchronic DM altered axonal and dendritic growth, patterns of synchronous Ca2+ oscillations (SCOs), and electrical spike activity (ESA) func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 104 publications
1
13
0
Order By: Relevance
“…In the current study, we demonstrated that BmK NSPK, a short-chain scorpion peptide, enhanced neurite outgrowth in a nonmonotonic manner. This nonmonotonic stimulation on the neurite outgrowth is consistent with activity-dependent neurite outgrowth by activation of VGSCs [ 52 ], activation of ryanodine receptors [ 32 ], or suppression of K v 1 channels [ 18 ]. We previously have reported a long-chain α-scorpion toxin (BmK NSP) that directly activated VGSCs by delaying inactivation of VGSCs [ 7 ].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In the current study, we demonstrated that BmK NSPK, a short-chain scorpion peptide, enhanced neurite outgrowth in a nonmonotonic manner. This nonmonotonic stimulation on the neurite outgrowth is consistent with activity-dependent neurite outgrowth by activation of VGSCs [ 52 ], activation of ryanodine receptors [ 32 ], or suppression of K v 1 channels [ 18 ]. We previously have reported a long-chain α-scorpion toxin (BmK NSP) that directly activated VGSCs by delaying inactivation of VGSCs [ 7 ].…”
Section: Discussionsupporting
confidence: 62%
“…Primary cultured SCNs display synchronized spontaneous calcium oscillations (SCOs) [ 7 ] that are balanced by excitatory and inhibitory neuronal inputs [ 28 , 29 ]. Alteration of the pattern of SCOs has been used to discover the neuroprotective compound for seizure [ 30 ] and pain [ 31 ], and also to discover neurotoxicants and explore their mechanisms [ 18 , 32 , 33 ]. We therefore explored the influence of BmK NSPK on SCOs in primary cultured SCNs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In agriculture, pesticides can improve crop yield and quality by killing or controlling insects, weeds, and detrimental microorganisms [ 1 ]. Pyrethroids are a large family of synthetic insecticides with chemical structures similar to that of the natural pesticide pyrethrum, which is produced by the chrysanthemum flower [ 2 ]. Cypermethrin (CMN, [cyano-(3-phenoxyphenyl)methyl] 3-(2,2-dichloroethenyl)-2,2-dimethylcyclopropane-1-carboxylate, PubChem CID: 2912) is a type II synthetic pyrethroid that is extensively used in residential, industrial, and agriculture applications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%